COAGULATION PROFILE IN PATIENT WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Abduganieva, E.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The aim of investigation was study of activity of the coagulation system in the patients with chronic obstructive pulmonary diseases by study of 3 markers of coagulation: fibrinogen, soluble fibrin monomer complexes and D-dimer. Material and Methods. There were elaborated patients with verified diagnosis COPD according to recommendations GOLD 2016, identification of the comorbidity phone in form of ischemic heart disease was performed with use of questionnaire Rose. Statistic processing of the results of investigation was made by the program Statistica 6.0. According to the severity degree of 65 patients 22 (33,8%) had severe III stage of severity and of 65 in 43 patients (66,2%) had extraordinary-severe(IV) stage of severity. Of 65 in 60 males mean age was 65,4±1,3 years. Duration of disease was in patients with severe stage COPD 15,23±1,9 years, and in patients with extremely severe stage of patients 15,56±1,9 years. Results of our study show that rising level of fibrinogen in patients with COPD was noted in 38 out of 65 patients (58,5% of cases); and elevating of the level of soluble fibrin-monomer complex was found in 59 out of 65 patients (90,8%) and increasing level of D-dimer, as a marker of pathological states of hemocoagulation, accompanied by intravascular fibrin accumulation, in patients with COPD was noted in 37 out of 65 patients 56,9% of cases). Conclusions: The results obtained in our study allow suggest that in patients with COPD there is state of tense coagulation stress that in absence of preventive measures may results in development of thrombogenic complications due to hypercoagulation